The Validity of the SF-36 in an Australian National Household Survey: Demonstrating the Applicability of the Household Income and Labour Dynamics in Australia (HILDA) Survey to Examination of Health Inequalities - Crosier, T; Butterworth, P (My University, 2004)
Background The SF-36 is one of the most widely used self-completion measures of health status. The inclusion of the SF-36 in the first Australian national household panel survey, the Household, Income and Labour Dynamics in Australia (HILDA) Survey, provides an opportunity to investigate health inequalities. In this analysis we establish the psychometric properties and criterion validity of the SF-36 HILDA Survey data and examine scale profiles across a range of measures of socio-economic circumstance. Methods Data from 13,055 respondents who completed the first wave of the HILDA Survey were analysed to determine the psychometric properties of the SF-36 and the relationship of the SF-36 scales to other measures of health, disability, social functioning and demographic characteristics. Results Results of principle components analysis were similar to previous Australian and international reports. Survey scales demonstrated convergent and divergent validity, and different markers of social status demonstrated unique patterns of outcomes across the scales. Conclusion Results demonstrated the validity of the SF-36 data collected during the first wave of the HILDA Survey and support its use in research examining health inequalities and population health characteristics in Australia.
BMC Public Health
Keywords: Surveys and Survey methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey methodology; Surveys and Survey Methodology